2020
DOI: 10.1037/rel0000269
|View full text |Cite
|
Sign up to set email alerts
|

The role of religious fundamentalism and tightness-looseness in promoting collective narcissism and extreme group behavior.

Abstract: The present study aims to understand the roles of religious fundamentalism and collective narcissism in predicting extreme behavior. It was hypothesized that religious fundamentalism may enhance collective narcissism and that this would in turn increase the tendency to endorse extreme behavior. It was also anticipated that perceptions of social tightness would moderate the indirect effect of religious fundamentalism on extreme behavior through collective narcissism.To test the hypotheses, we collected data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 78 publications
(140 reference statements)
0
17
0
1
Order By: Relevance
“…Similarly to nationalism, national collective narcissism has also been linked to support for extreme intergroup violence and aggression, for instance military aggression in the US (Golec de Zavala et al, 2009). In Sri Lanka, Morocco and Indonesia, collective narcissism Running head: NATIONALISM AS COLLECTIVE NARCISSISM 7 was also associated with support for ideological extremism and political violence, especially in radical social contexts (e.g., when participants belonged to known terrorist organisations; Jasko et al, 2019;Yustisia, Putra, Kavanagh, Whitehouse, & Rufaedah, 2019). Support for such actions seems to be especially likely when in-group members feel somehow threatened.…”
Section: Collective Narcissism and Intergroup Relationsmentioning
confidence: 99%
“…Similarly to nationalism, national collective narcissism has also been linked to support for extreme intergroup violence and aggression, for instance military aggression in the US (Golec de Zavala et al, 2009). In Sri Lanka, Morocco and Indonesia, collective narcissism Running head: NATIONALISM AS COLLECTIVE NARCISSISM 7 was also associated with support for ideological extremism and political violence, especially in radical social contexts (e.g., when participants belonged to known terrorist organisations; Jasko et al, 2019;Yustisia, Putra, Kavanagh, Whitehouse, & Rufaedah, 2019). Support for such actions seems to be especially likely when in-group members feel somehow threatened.…”
Section: Collective Narcissism and Intergroup Relationsmentioning
confidence: 99%
“…Although there are many practical impediments to conducting research with groups whose members have sacrificed their lives in appreciable numbers, and the evidence drawn upon here is limited, efforts to access more participants in other troubled regions of the world are ongoing. Data collection using much the same methods as those employed in Libya in the research described above has been undertaken among fundamentalist Islamist groups (Kavanagh et al, in preparation; Yustisia et al, under review), and efforts are also underway to collect data from convicted terrorists in prison.…”
Section: Shared Essence Fusion and Willingness To Fight And Die Formentioning
confidence: 99%
“…Research by Yustisia et al (2020) and Cavell (1990) stated that the understanding of the importance of a good life and dignified life needs to be instilled as the values of character education centered on teaching that prioritizes the contents of academic meaning values and practices to be explained and studied, so that it can become a set of qualities of moral virtue known and understood by students, where value clarification prioritizes the process of moral reasoning and the selection of values that students must have. Furthermore, Li and Zizzi (2018) and Lickona (1991) also suggested that the focus of strengthening strong character development for children is on the growth of moral character that prioritizes behavior to reflect the acceptance of values and emphasize the element of motivation, as well as aspects of personality that are relatively stable which will direct individual actions.…”
mentioning
confidence: 99%